(untitled) (Research, Society and Development, 2021)
The objective of this study was to find out how nursing care is provided to pregnant women diagnosed with HIV during prenatal care and identify the nursing actions developed for pregnant women diagnosed with HIV during prenatal care and their contributions. This is an integrative literature review study, with a quantitative approach, with a search conducted between February and March 2021 in the databases of the Scientific Electronic Library Online, Latin American and Caribbean Literature on Health Sciences, Nursing Database and Medical Literature Analysis and Retrieval System Online using the Descriptors in Health Sciences: HIV Pregnant Woman, Nursing Care and Prenatal Care, through the PICo acronym. At first, 535 studies were retrieved, however, after applying the inclusion criteria (original research that answered the research question and published in Portuguese, English and Spanish) and exclusion (duplicate studies, theses, dissertations, monographs, manuals, editorials, review studies), 21 studies were retrieved. The importance of beginning the assistance during planning and not only during prenatal care is perceived, this being an opportune moment to investigate the couple’s clinical history, possible situations of risk and vulnerability in order to plan a safe pregnancy for mother and fetus. Furthermore, it is observed that the integral, holistic and humanized assistance to pregnant women diagnosed with HIV during prenatal care has contributed to the reduction of vertical transmission of the disease.